Plunder a memoir of family property and Nazi treasure - Kaiser, Menachem 1985- (Houghton Mifflin Harcourt, 2021)
"From a gifted young writer, the story of his quest to reclaim his family's apartment building in Poland--and of the astonishing entanglement with Nazi treasure hunters that follows"--
Keywords: Juden; Nationalsozialismus; Enteignung; Rückforderung; Mehrfamilienhaus; Sosnowitz; Holocaust, Jewish (1939-1945) / Poland / Sosnowiec (Województwo Śląskie) / Reparations; Kaiser, Meir Menachem / 1921-1977 / Family; Inheritance and succession / Poland; Jewish property / Poland / Sosnowiec (Województwo Śląskie) / 20th century; World War, 1939-1945 / Claims; World War, 1939-1945 / Destruction and pillage / Poland; Kaiser family; Treasure troves / Poland; Sosnowiec (Województwo Śląskie, Poland) / History / 20th century; Destruction and pillage; Families; Inheritance and succession; Jewish property; Treasure troves; War reparations; Poland; Poland / Sosnowiec (Województwo Śląskie); HISTORY / World; 1900-1999; Claims; History